Attentional disorders in patients with complex partial epilepsy - Stella, Florindo [UNESP]; Maciel, Jayme Antunes (FapUNIFESP (SciELO), 2003)
A study of concentrated attention patterns in epileptic patients was conducted with the objectives: characterization of the patients' epileptic condition; assessment of the concentrated attention levels in epileptic and nonepileptic individuals; comparison of the attention levels of the two groups. An evaluation was performed of 50 adult outpatients with complex partial seizures and 20 non-epileptic individuals (comparative group) at the Neuroepilepsy Ambulatory Unit, State University of Campinas SP, Brazil. Method: characterization of seizure types, frequency and duration; concentrated attention assessment (Concentrated Attention Test - Toulouse-Piéron); comparison of the epileptic with non-epileptic individuals. Results: A statistically significant difference was observed between the groups with regard to Correct Response, Wrong Response and No Response. A difference was observed in relation to Time, but it was statistically insignificant. The epileptic patients presented inferior cognitive performance in relation to concentrated attention when compared with the non-epileptic individuals, findings compatible with the clinical complaints.
Keywords: Attention; Complex partial epilepsy; Neuropsychology; adult; attention deficit disorder; clinical article; cognition; complex partial seizure; controlled study; focal epilepsy; human; outpatient; statistical significance; Adult; Case-Control Studies; Cognition Disorders; Epilepsy, Complex Partial; Female; Humans; Male; Middle Aged; Neuropsychological Tests; Statistics, Nonparametric; Time Factors